Sticking with it: a multi-sensor tag to reveal the foraging ecology and fine-scale behavior of elusive durophagous stingrays - Cecilia M. Hampton; Breanna C. DeGroot; Lauran R. Brewster; Kim Bassos-Hull; Benjamin A. Metzger; T. Aran Mooney; Matthew J. Ajemian (Animal Biotelemetry)
Abstract Large, durophagous (shell-crushing) rays are hypothesized to play a pivotal role in marine food webs, yet information on their fine-scale behavioral ecology is limited due to their elusive nature and challenges with tagging these morphologically unique animals. Here we sought to develop and apply a novel, minimally invasive tagging approach to investigate the movements, behaviors, and ecological interactions of these understudied species. Our custom-adapted multi-sensor device integrated a CATS inertial motion unit (IMU) and camera package equipped with a broadband (0-22050 Hz) hydrophone, an Innovasea V-9 coded acoustic transmitter, and a Wildlife Computers satellite transmitter (363-C). Fully assembled, the package is 24.1 x 7.6 x 5.1 cm, weighs 430 g in air, and is positively buoyant in water. The units are attached to the anterior dorsal region of a ray via two silicone suction cups, and a 24-h or 48-h galvanic timed release is strapped to plastic hooks on the cartilage of each spiracle. Through aquaria-based captive trials (N = 46), and field trials (N = 13) in Bermuda, retention times on whitespotted eagle rays (Aetobatus narinari) ranged from 0.1 to 59.2 h, (mean of 12.1 h ± 11.9 SD), with 7 out of 13 field deployments lasting >18 h, and were significantly increased by the use of the spiracle strap. Data from the Inertial Measurement Unit (IMU) suggest postural and pitching motions related to feeding, while video and audio data can capture shell fracture acoustics (i.e., predation). We expect this tool to provide insight into in situ behaviors of multiple species of benthopelagic rays, although we recommend future researchers incorporate captive testing where possible prior to field experimentation.